Dekolorisasi dan deoilisasi parafin menggunakan adsorben zeolit, arang aktif dan produk pirolisis batu bara - Bardi Murachman; Eddie Sandjaya Putra; Wulandary Wulandary (Jurnal Rekayasa Proses, 2014)
Indonesian wax production was reaching 50277 barrels in 2009. Although the wax production rate in Indonesia is quite high, it is still not enough to fulfill the demand. Therefore, Indonesia has to import wax from China. Unfortunately, Indonesian wax qualities, especially related to colour and hardness, are less compared with those from China. Local wax is more brownish yellow, soft and easily melted compared with the wax from China which is whiter, harder and difficult to melt.Many research activities have been conducted to improve quality of local wax. Among of them is with the use of adsorption method with adsorbent.Various adsorbents can be used, including activated carbon, zeolite, and coal pyrolysis product. The present work aim was to find the ability of forementioned adsorbent in purpose to improve the quality of wax, i.e. colour and texture, by decolorization dan deoilization process. Adsorbent was added to the wax at 90°C and mixing was then conducted. Parameters under investigation were the influence of the ratio of wax to adsorbent and the optimum mixing time.Based on reduction of oil content and colour intensity, the best wax -adsorbent ratio was 6 : 6 with a mixing time of 50 minutes. Zeolite gives the best adsorption properties and high effectivity in deoilization and decolorization process.